PENGELOLAAN KEGIATAN PEMBELAJARAN BERBASIS TEKNOLOGI PENDIDIKAN - Zaenal Abidin (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This research focuses about management of school activity base on the education technology. This research???s target is to know the concept of education technology, technological type of education, and how to manage the school activity being based on education technology. This research method is qualitative. Result of research indicate that to manage the school activity being based on educational technology, hence a teacher or instructor energy claimed to comprehend the technological concept of itself education and able to apply it or exploit in course of learning to teach.